Islamic Educational Innovation: Exploring Modern Pedagogical Approaches in Islamic Institutions and Their Impact on Students’ Cognitive and Ethical Development - Mukhlis Mukhlis; Helene Knudstad; Md. Sultan Mahmud; Najeeb Yahya; Mowafg Masuwd (Al-Mukhlashin: Jurnal Multidisiplin Ilmu, 2025)
Islamic educational institutions have historically played a pivotal role in shaping the intellectual and ethical development of students. This research examines modern pedagogical innovations within Islamic education systems and assesses their impact on students’ cognitive and ethical development. Through case studies of Islamic schools, universities, and other educational settings in both traditional and contemporary contexts, the study highlights the integration of Islamic principles with innovative teaching methods. The research emphasizes the role of technology, experiential learning, and student-centered approaches in fostering critical thinking, moral reasoning, and community engagement. Data collected from surveys, interviews, and classroom observations provide a comprehensive analysis of how these innovations are being implemented and their effectiveness in nurturing well-rounded individuals. The paper concludes with recommendations for further integrating modern pedagogical techniques within Islamic education, particularly in the context of global educational challenges.